The Effect of Digitalizing Vocabulary Course Book for The Second Semester Students - Enjang Saraswati; Dwi Putri Hartiningsari (STKIP PGRI Trenggalek, 2021)
The aim of the experimental research is to know any effect or not after using the Digitalizing Vocabulary coursebook. This research was using two types of variables. The first variable was the application of Digitalizing Vocabulary coursebook. The second variable was students’ interest in vocabulary learning. The subject of the research is second-semester student of the English language education department in STKIP PGRI Trenggalek. The instrument is to collect the data of this research by pretest and posttest. After the data was collected the researcher analyzed the data by using an independent sample T-Test. Based on test the Sig. (2-tailed) of posttest are 0,000 < 0,05, then as the basic rules of making the independent sample t-test, it can be concluded that H0 is rejected and Ha is accepted. The result of the test conducted by the researcher; Digitalizing coursebook is interactive than the printed book for students of the English language education department in STKIP PGRI Trenggalek.